The Implementation of Project Based Learning Model Assisted with WhatsApp Messenger - Herman Jufri Andi; Ulfatul Fitriyah; Nilna Mely Dina; Mohammad Lutfiyadi (Jurnal Pembelajaran Fisika, 2019)
This study aims to determine the effect and effectiveness of the Project Based Learning (PjBL) model assisted with WhatsApp Messenger compared to the Problem Based Learning (PBL) Model, in terms of the creative thinking skill of high school students in physics learning. This study used quasi experimental model with non-equivalent control group design. The data were analyzed by using independent samples t-test and effect size test. Based on the tests, it can be concluded that there are significant effect on the implementation of PjBL model assisted with WhatsApp Messenger on the creative thinking skill of high students in physics learning and PjBL model assisted with WhatsApp Messenger is more effective than the PBL model. Keywords: creative thinking skills, effect size, PBL, PjBL, WhatsApp Messenger DOI: http://dx.doi.org/10.23960/jpf.v7.n1.201901